Quantum States of ABR Formulation for Josephsons Tunneling in ThxDUO2 Nano Material for 516 tesla at LHC Cyclotron - Hardiyanto, Moh. (Program Studi Pendidikan Fisika UHAMKA, 2015)
The convergence quantum states of free covariant equation in Einsteins space with quantum condition is studied using the ABR (Abrikosov-Balseiro-Russell) formulation in convergence approximation for Josephson tunneling is important role for determine of neutrino particle existing, especially after Cerenkovs effect for 516 tesla super magnetic at Large Hadron Collider (LHC) Cyclotron in CERN, Lyon, France based on ThxDUO2 nano material. This approaching will be solved the problem for determine the value of interstellar Electrical Conductivity (EC) on DUO2 chain reaction, then the post condition of muon has been known exactly. In this research shown the value of EC is 4.32 x 10-6 eV at 378 tesla magnetic field for 2.1 x 104 ci/mm fast thermal neutron floating in 45.7 megawatts adjusted power of CERNâs Cyclotron. The resulted by special Electron-Scanning-Nuclear-Absorption (ESNA) shown any possibilities of Josephsons tunneling must be boundary by muon particles without neutrino particle existing for 450 - 565 tesla magnetic field on UO2 more enrichment nuclear fuel at CERN, whereas this research has purpose for provide the mathematical formulation to boundary of muons moving at nuclear research reactor to a high degree of accuracy and with Catch-Nuc, one of nuclear beam equipment has a few important value of experimental effort. Keywords: ABR formulation, EC value, ThxDUO2 nano material, super magnetic field value.